Programmable PFC based hybrid multipulse power rectifier for utility interface of power electronic converters - De Freitas, L. C. Gomes; Coelho, E. A A; Finazzi, A. P.; Simoes, M. G.; Canesin, C. A. [UNESP]; De Freitas, L. C. (Institute of Electrical and Electronics Engineers (IEEE), 2005)
In this paper it is proposed a novel hybrid three-phase rectifier capable to achieve high input power factor (PF), and low total harmonic distortion in the input currents (THDI). The proposed hybrid high power rectifier is composed by a standard three-phase 6-pulses diode rectifier (Graetz bridge) with a parallel connection of single-phase Boost rectifiers in each three-phase rectifier leg. Such topology results in a structure capable of programming the input current waveform and providing conditions for obtaining high input power factor and low harmonic current distortion. In order to validate the proposed hybrid rectifier, this paper describes its principles of operation, with detailed experimental results and discussions on power rating of the required Boost converters as related to the desired total harmonic current distortion. It is demonstrated that only a fraction of the output power is processed through the Boost converters, making the proposed solution economically viable for very high power installations, with fast pay back of the investment. Moreover, retrofitting to existing installations is also feasible since the parallel path can be easily controlled by integration with the existing de-link. A prototype rated at 6 kW has been implemented in laboratory and fully demonstrated its operation, performance and feasibility to high power applications. © 2005 IEEE.
Keywords: Electric currents; Electric network topology; Electric utilities; Harmonic distortion; Investments; Power converters; Waveform analysis; Harmonic current distortion; Single-phase Boost rectifiers; Three-phase 6-pulses diode rectifier; Electric rectifiers